2004
DOI: 10.1002/cne.20224
|View full text |Cite
|
Sign up to set email alerts
|

Target‐specific differences in somatodendritic morphology of layer V pyramidal neurons in rat motor cortex

Abstract: Dendritic geometry has been shown to be a critical determinant of information processing and neuronal computation. However, it is not known whether cortical projection neurons that target different subcortical nuclei have distinct dendritic morphologies. In this study, fast blue retrograde tracing in combination with intracellular Lucifer yellow injection and diaminobenzidine (DAB) photoconversion in fixed slices was used to study the morphological features of corticospinal, corticostriatal, and corticothalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 84 publications
7
61
0
Order By: Relevance
“…In this study, we confirmed that CCS and CPn cells are mutually exclusive groups using doublefluorescence markers. Apical dendritic tufts are different in size among pyramidal cell subtypes (Hallman et al, 1988;Hübener et al, 1990;Kasper et al, 1994;Gao and Zheng, 2004). In addition to their striking differences in axonal projection, we found significant morphological differences in their apical tuft structures (Fig.…”
Section: Corticostriatal Cell Heterogeneity and Their Intracortical Cmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, we confirmed that CCS and CPn cells are mutually exclusive groups using doublefluorescence markers. Apical dendritic tufts are different in size among pyramidal cell subtypes (Hallman et al, 1988;Hübener et al, 1990;Kasper et al, 1994;Gao and Zheng, 2004). In addition to their striking differences in axonal projection, we found significant morphological differences in their apical tuft structures (Fig.…”
Section: Corticostriatal Cell Heterogeneity and Their Intracortical Cmentioning
confidence: 79%
“…In the neocortex, pyramidal cells projecting to the same target areas are aggregated within given cortical layers, with each layer containing several projection types (Jones, 1984;Kasper et al, 1994;Gao and Zheng, 2004). Even within microregions of the same cortical layer, there can exist several projection cell types (Lévesque et al, 1996b;Vercelli et al, 2004;Gabbott et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1 B, E, 2A), and CTh cells were localized in both L5a and L6 (Figs. 1 D, 2A) (Deschênes et al, 1994;Gao and Zheng, 2004). Dual retrograde labeling revealed that L5 PRCprojecting cells were overlapped with the upper CCS group (Fig.…”
Section: Axon Collateralization Of Prcprojecting Cells To Subcorticalmentioning
confidence: 89%
“…Intracellular injection of neurons in lightly fixed slices was performed as previously described with modifications (37,38). All animals underwent intracellular injections of LY.…”
Section: Methodsmentioning
confidence: 99%